PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS VI - Anggun Nastiti; Sandi Budiana; Hida Wahida Chusen (STKIP Subang, 2023)
The aim of this Collaborative Classroom Action Research (PTKK) is to find out and obtain data on how the Problem Based Learning (PBL) learning model can improve student learning outcomes in Class VI Social Sciences learning at Kawungluwuk State Elementary School, semester 1 of the 2023/2024 academic year. Classroom action research uses the Kemmis and Mc Tanggart model design. Stages of conducting research through planning, implementation, observation and reflection. The results of the research show that there is an increase in student learning outcomes from each cycle, where the gains in the pre-cycle were with an average value of 67.1. In cycle I with an average value of 75.37 and in cycle II with an average value of 84.63 with completion percentage 78%. It can be concluded that learning outcomes between pre-cycle to cycle I and cycle II have increased learning outcomes using the Problem Based Learning learning model.